The Critical Roles of Localization and Physiology for Understanding Parietal Contributions to Memory Retrieval. (December 2013) - Nelson, Steven M.; McDermott, Kathleen B.; Wig, Gagan S.; Schlaggar, Bradley L.; Petersen, Steven E.
Functional magnetic resonance imaging (fMRI) studies of recognition memory ubiquitously demonstrate retrieval-related activity in left lateral parietal cortex (LLPC) when contrasting studied ("old") items with unstudied ("new") items. Recent work demonstrates that there is considerable functional–anatomical heterogeneity in LLPC. One implication of this observation is that single- or dual-process models fall short of characterizing LLPC contributions to memory retrieval. Instead of considering LLPC as a single entity, functional accounts must be given for each of the distinct regions that show retrieval-related effects; we posit there are a minimum of four such regions and very likely more. Identification of these LLPC regions requires careful analysis to map the boundaries and the extent of the regions precisely. In addition, characterizing the functional responses as activations or deactivations relative to baseline will be crucial in understanding the underlying cognitive processes. Considering LLPC in both memory and "nonmemory" domains will also illuminate the contribution of these regions, because it is certainly unlikely they serve only the domain of memory retrieval.